SARS-CoV-2 recurrent RNA positivity after recovering from coronavirus disease 2019 (COVID-19): a meta-analysis - Mattiuzzi, Camilla; Henry, Brandon M.; Sanchis-Gomar, Fabian; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Isolation of subjects with active severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a pivotal preventive measure in the ongoing coronavirus disease 2019 (COVID-19) pandemic. A growing number of studies reported cases of recurrent SARS-CoV-2 RNA positivity following disease recovery, which were identified with a critical literature search and then meta-analyzed in this article. Materials and Methods: A digital search was performed in Medline and Web of Science, using the keywords “coronavirus disease 2019” OR “COVID-19” OR “severe acute respiratory disease 2” OR “SARS-CoV-2” AND “recurrence” OR “repositivization” OR “retesting”, without date or language restrictions. Recovery was defined as resolution of symptoms, with at least two consecutive negative molecular tests. Results: A total number of 17 studies, with 5,182 COVID-19 patients, were included. SARS-CoV-2 recurrent RNA positivity in recovered COVID-19 patients ranged between 7-23% across the studies, with follow-up testing between 1-60 days. The estimated cumulative rate of SARS-CoV-2 recurrent RNA positivity was 12% (95% confidence interval, 12-13%; I2, 74%). Conclusions: Repeated molecular testing on respiratory tracts specimens at 1 and 2 months after recovery from COVID-19 is strongly advisable for early identification, isolation and clinical management of subjects with SARS-CoV-2 recurrent RNA positivity.